Government Spending Categories and their Different Impact on Private Consumption and the Real Exchange Rate - Baldi, Guido (Journal of Advanced Research in Economics and International Business, 2013)
The macroeconomic literature has found puzzling effects of government spending on private consumption, the real exchange rate and the terms of trade. Some authors find that private consumption increases after a shock to government spending, while others report a decrease. The same ambiguity can be found for the real exchange rate and the terms of trade. Our paper offers an intuitive explanation for these divergent results by distinguishing between productive and unproductive government spending. We show within a calibrated two-sector DSGE model that the two government spending categories have different effects on private consumption, the real exchange rate and the terms of trade. Hence, our findings suggest that the composition of government spending matters not only for long-run growth, but also impacts on the short-run.